2020
DOI: 10.1055/a-1224-3347
|View full text |Cite
|
Sign up to set email alerts
|

Colitis cystica profunda mimicking mucinous adenocarcinoma of the rectum diagnosed by endoscopic submucosal dissection

Abstract: Video 1 Endoscopic submucosal dissection of colitis cystica profunda in the lower rectum along with resection of the tumor using the pocket-creation and clip-with-line methods. ▶ Fig. 3 The resected specimen. a Photograph of the resected specimen, approximately 9 × 6 cm in size. b Macroscopic view of the resected specimen, showing several cystic lesions containing mucin. c Histological images of the resected specimen stained with hematoxylin and eosin, showing colitis cystica profunda without findings of dyspl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Conservative treatment is ineffective, and surgical resection is required when symptoms are persistent or severe, such as bowel obstruction, bleeding, or rectal prolapse 18,19 . In recent years, endoscopic submucosal dissection, with the advantages of rapid recovery, minimal trauma, and preservation of colonic integrity, has been widely used in treating CCP 20 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conservative treatment is ineffective, and surgical resection is required when symptoms are persistent or severe, such as bowel obstruction, bleeding, or rectal prolapse 18,19 . In recent years, endoscopic submucosal dissection, with the advantages of rapid recovery, minimal trauma, and preservation of colonic integrity, has been widely used in treating CCP 20 …”
Section: Discussionmentioning
confidence: 99%
“…18,19 In recent years, endoscopic submucosal dissection, with the advantages of rapid recovery, minimal trauma, and preservation of colonic integrity, has been widely used in treating CCP. 20 In conclusion, CCP is a rare disease that is difficult to diagnose and easily misdiagnosed as other occupying lesions of the intestine because of its low incidence, lack of specificity in clinical and endoscopic manifestations, and lack of awareness among physicians in various disciplines. Once misdiagnosed, it brings unnecessary painful surgical resection to patients and poses risks to physicians.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conservative treatment is ineffective and surgical resection is required when symptoms are persistent or severe, such as bowel obstruction, bleeding, or rectal prolapse [18,19] . In recent years, endoscopic submucosal dissection (ESD), with the advantages of rapid recovery, minimal trauma, and preservation of colonic integrity, has been widely used in the treatment of CCP [20] .…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of CCP is mostly conservative and surgery is only suggested in patients with complications such as obstruction and bleeding. However, case reports recently showed that it not only mimicked well-differentiated rectal adenocarcinoma [3], but also accompanied by adenocarcinoma on the surface…”
Section: Discussionmentioning
confidence: 99%